أثر سياسة التحرير المالي على النمو الاقتصادي: دراسة قياسية لحالة الجزائر - خربوش، محمد Kherboush, Mohammed; زغودي، أحمد حبيب; بن لدغم، فتحي (جامعة قاصدي مرباح ورقلة, 2017)
إن وجود نظام مالي قوي ومتطور هو شرط أساسي من شروط تحقيق التنمية الاقتصادية في أي بلد، فمن خلال دراستنا لأثر سياسة التحرير المالي على النمو الاقتصادي في الجزائر خلال الفترة الممتدة من 2014-1990 باستعمال طريقة التكامل المتزامن ونموذج متجه تصحيح الخطأ. أظهرت نتائج اختبار جوهانسن وجود علاقتي تكامل مشترك وهذا يعني وجود علاقة توازنيه طويلة الأجل بين سياسة التحرير المالي والنمو الاقتصادي في الجزائر. ومن خلال تقدير نموذج العلاقة في المدى الطويل باستخدام طريقة المربعات الصغرى المصححة كليا توصلنا إلى وجود علاقة إيجابية وطويلة الأجل بين سياسة التحرير المالي والنمو الاقتصادي في الجزائر.
The existence of a strong and well-developed financial system is an essential condition for achieving economic development in any country, through our study of the impact of financial liberalization policy on economic growth in Algeria during the period of 1990-2014 using the method of cointegration and VECM model. Johansen test results showed the presence of two cointegration relationships and this means that there is a long-run equilibrium relationship between financial liberalization and economic growth in Algeria. By estimating the relationship model in the long run using the FM OLS method we reached a positive and long-term relationship between financial liberalization and economic growth in Algeria.
Keywords: النمو الاقتصادي -- الاقتصاد الجزائري -- التحرير المالي -- الاستقرار الاقتصادي -- التحرير المصرفي